2015
DOI: 10.1038/srep11852
|View full text |Cite
|
Sign up to set email alerts
|

Can plasmonic Al nanoparticles improve absorption in triple junction solar cells?

Abstract: Plasmonic nanoparticles located on the illuminated surface of a solar cell can perform the function of an antireflection layer, as well as a scattering layer, facilitating light-trapping. Al nanoparticles have recently been proposed to aid photocurrent enhancements in GaAs photodiodes in the wavelength region of 400–900 nm by mitigating any parasitic absorption losses. Because this spectral region corresponds to the top and middle sub-cell of a typical GaInP/GaInAs/Ge triple junction solar cell, in this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Although front side NP arrays have been shown to improve in III-V solar cells in the past [8,9], these examples were benchmarked against devices with non-optimal antireflection, as opposed to the optimised double layer ARC used as comparison here. It has already been shown that Al NPs are unlikely to lead to an improved anti-reflection compared to an optimised ARC [17]. We add to this by demonstrating clearly the limitations of enhancing the photocurrent of highefficiency solar cells using Al or AlInP NP arrays on the front face, even in the case where the absorbing layer is extremely thin and requires absorption enhancement via oblique photon scattering.…”
Section: B Simulation Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Although front side NP arrays have been shown to improve in III-V solar cells in the past [8,9], these examples were benchmarked against devices with non-optimal antireflection, as opposed to the optimised double layer ARC used as comparison here. It has already been shown that Al NPs are unlikely to lead to an improved anti-reflection compared to an optimised ARC [17]. We add to this by demonstrating clearly the limitations of enhancing the photocurrent of highefficiency solar cells using Al or AlInP NP arrays on the front face, even in the case where the absorbing layer is extremely thin and requires absorption enhancement via oblique photon scattering.…”
Section: B Simulation Resultsmentioning
confidence: 71%
“…All other layer thicknesses are as in the experimental Sample Set 1. To simplify the study, only the performance of the In 0.01 GaAs middle cell is monitored, since the difficulty of achieving good anti-reflection in both upper subcells simultaneously has already been investigated by Yang [17]. We choose not to use a drift-diffusion model here, but instead make the simplifying assumption that all photogenerated carriers in the middle cell are extracted as current.…”
Section: A Solar Cell Structure and Figures Of Meritmentioning
confidence: 99%
See 1 more Smart Citation
“…To further increase the conversion efficiency it is necessary to enhance light absorption, increase carrier collection, or reduce the energy loss due to thermalization. Several strategies have been proposed to increase the conversion efficiency in III–V multi-junction solar cells3456. For example, a new material engineering technique has been developed for maintaining high thermal homogeneity at the wafer surface, which expands the bandgap engineering possibilities for improving the efficiency in III–V multi-junction solar cells4.…”
mentioning
confidence: 99%
“…For example, a new material engineering technique has been developed for maintaining high thermal homogeneity at the wafer surface, which expands the bandgap engineering possibilities for improving the efficiency in III–V multi-junction solar cells4. Also, metal nanoparticles have been introduced on the illuminated surface of III–V multi-junction solar cells for producing strong light scattering and light trapping, which is beneficial for carrier generation in the absorbing region56. A 15% increase of conversion efficiency has been implemented by introducing Au nanoclusters on top of the III–V multi-junction solar cells5.…”
mentioning
confidence: 99%